Coating of PLA-nanoparticles with cyclic, arginine-rich cell penetrating peptides enables oral delivery of liraglutide - Uhl, Philipp; Sauter, Max; Storck, Philip; Tursch, Anja; Özbek, Suat; Leotta, Karin; Fidelj, Veronika; Kleist, Christian; Fricker, Gert; Mier, Walter (Nanomedicine. Nanotechnology, biology and medicine, 2020)
Until today, the oral delivery of peptide drugs is hampered due to their instability in the gastrointestinal tract and low mucosal penetration. To overcome these hurdles, PLA (polylactide acid)-nanoparticles were coated with a cyclic, polyarginine-rich, cell penetrating peptide (cyclic R9-CPP). These surface-modified nanoparticles showed a size and polydispersity index comparable to standard PLA-nanoparticles. The zeta potential showed a significant increase indicating successful CPP-coupling to the surface of the nanoparticles. Cryo-EM micrographs confirmed the appropriate size and morphology of the modified nanoparticles. A high encapsulation efficiency of liraglutide could be achieved. In vitro tests using Caco-2 cells showed high viability indicating the tolerability of this novel formulation. A strongly enhanced mucosal binding and penetration was demonstrated by a Caco-2 binding and uptake assay. In Wistar rats, the novel nanoparticles showed a substantial, 4.5-fold increase in the oral bioavailability of liraglutide revealing great potential for the oral delivery of peptide drugs.
Available online 27 November 2019
Gesehen am 17.04.2020